Scouts' strike at St Anne's College, Oxford University, 1972 (1972)
1972 1960-2000 "Scouts' strike at St Anne's College, Oxford University, 1972" [EP0156], 1972 Cut-backs in college budgets led to compulsory redundancies among domestic staff at St Anne's College, Oxford University. The remaining staff took strike action throughout the 1972 Michaelmas [Autumn] term, also protesting the low wages paid to cleaners. St Anne's College was a women-only college until 1979 and reports suggest that some undergraduates joined the picket line.